TOTAL ANTIOXIDANT CAPACITY AND ANTIHYPERLIPIDEMIC ACTIVITY OF ALKALOID EXTRACT FROM AERIAL PART OF ANETHUM GRAVEOLENS L. PLANT - Al–Fartosy, Adnan J.M.; Zearah, Sameerah Ahmed; Alwan, Nawras A. (European Scientific Journal, ESJ, 2013)
Compounds of pharmacological interest (alkaloids) were extracted and the results revealed that the extract consist of three alkaloid compounds (A, B & C). Compound (A) has been isolated from Anethum graveolens L. aerial parts by column chromatography using C6H6 : Ethanol (9:1) solvent as eluent. It was found that simultaneous administration of alkaloid compound A (500 mg/kg/day) and cholesterol for 4 weeks, significantly (P<0.01) prevented the rise in serum TC, TG, LDL-cholesterol, VLDL-cholesterol, atherogenic index and significantly (P<0.01) increased TAC and HDL-cholesterol as compared to cholesterol fed control rabbits. Thus, the results indicate antioxidant and hypolipidemic effect of alkaloid compound A of Anethum graveolens L. aerial parts.